Super-multifactorial survey YHAB revealed high prevalence of sleep apnoea syndrome in unaware older adults and potential combinatorial factors for its initial screening - Tanaka, Yuji; Ando, Takashi; Mochizuki, Kazuki; Igarashi, Satoshi; Tsuchiya, Kyoichiro; Saito, Kozo; Ito, Yasumi; Yamagata, Zentaro; Iwasaki, Masaru; YHAB Health Data Survey Group 2020,; Ando, Daisuke; Baba-Mori, Naana; et al. (Frontiers in Aging, 2022)
Study Objectives: Aging is a risk factor for sleep apnoea syndrome (SAS), which is associated with lower quality of life and sudden mortality. However, SAS is often overlooked in older adults without suspicions. Therefore, this study aimed to evaluate SAS incidence and 48 other general factors in older adults. Methods: This cross-sectional study included all non-caregiver-certified, healthy individuals (N=32) who survived during the long-term cohort study and agreed to participate in apnoea-hypopnoea index (AHI) measurement (aged 83–95 years). AHI and 48 other general factors were evaluated, and simple linear regression analysis was used to identify potential AHI-related factors. Stepwise evaluation was further performed using multiple linear regression analyses. Results: Although no individuals were previously diagnosed with SAS, 30 (93.75%) participants had some degree of SAS (AHI >5/h), and 22 (68.75%) had severe or moderate SAS (AHI >15/h). Compared with typical single risk factors represented by body mass index, combining daily steps and other factors improved the fit to the multiple linear regression. Combining daily steps and body mass index improved the fit for males and combining daily steps and red blood cell count improved the fit for females. Conclusions: SAS was highly prevalent in unaware healthy Japanese older adults; combinations of daily steps and body mass index, and daily steps and red blood cell count may predict AHI in such individuals without the need for a specific AHI test.